2003
DOI: 10.2307/4003840
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Row Spacing on Digitaria eriantha Production and Digestibility

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…This species can be established using stolon scions or seeds. Although D. eriantha is associated with well managed vegetation, this species also becomes abundant in moderately severely overgrazed vegetation (Theunissen 1997 This research is a follow -up of another, previous study in D. eriantha (Gargano et al 2003) where yields responded to N fertilization, mainly when it was split rather than applied at once. In that study, no definite yield response was observed when sowing at different row spacings.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…This species can be established using stolon scions or seeds. Although D. eriantha is associated with well managed vegetation, this species also becomes abundant in moderately severely overgrazed vegetation (Theunissen 1997 This research is a follow -up of another, previous study in D. eriantha (Gargano et al 2003) where yields responded to N fertilization, mainly when it was split rather than applied at once. In that study, no definite yield response was observed when sowing at different row spacings.…”
Section: Introductionmentioning
confidence: 72%
“…Hanson et al (1978) reported that applying N fertilizer after the first cutting in 3 perennial grass species increased second cutting forage N content, indicating forage responded more from a split than from a single application. Gargano et al (2003) also reported that dry matter yields were greater in D. eriantha under a split than bulk application of N fertilizer. Bittman and Kowalenko (1998) concluded that split applications could have practical advantages, even with no yield increases, by evening out the yield and crude-protein concentration over the season.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations